Reducing the proportion of Pinus tabuliformis planted in mixed coniferous-broad forest stabilizes the microbiological community composition - Li, Zixing; Wang, Ran; Gao, Runmei; Hu, Zhenhua; Zhang, Mengtao (Frontiers in Plant Science, 2025)
BackgroundPiuns tabuliformis is an evergreen conifer species in North China and plays an important role in maintaining ecological security in North China. Soil microbiological, which are susceptible to disturbance by various external factors, is an important indicator of soil health and are crucial for maintaining soil biodiversity and ensuring the stability of ecosystem functions. However, the mechanisms driving changes in soil properties and soil microbiological community composition under different percentages of P. tabuliformis plantations are still poorly understood.MethodsIn this study, we investigated soil properties and microbiological community composition in four forests with different percentages of P. tabuliformis plantation (PT10%, PT20%, PT60% and PT100%) in Zhongtiao Mountain.ResultsThe results showed that lowering the planting ratio of P. tabuliformis in mixed conifer-broad forests could improve soil pH and increase the nutrient reserves in the soil. The relative abundance of Ascomycota in the soil increased with the reduction of the planting proportion of P. tabuliformis. Co-occurrence network analyses showed that soil microbiological community composition was more stable in forests with lower percentages of P. tabuliformis plantings (PT20%).ConclusionThis study showed that soil microbiological community composition was more stable in forests with a low percentage of P. tabuliformis planting and a rich forest canopy of tree species. The planting proportion of P. tabuliformis is an important factor influencing soil microbiological community composition, which provides a new theoretical basis for rational management of mixed coniferous and broadleaf forests in warm-temperate continental climate zones.